Impact of human activities on the natural environment and agricultural land soil in Penjwen district - صابر, سايا سلام صابر; لایق, سەروەر عبدللە محمد لایق; صابر, ا.د. سايا سلام صابر; لایق, سەروەر عبدللە محمد لایق (Sulaimani Journal for Humanities, 2025)
The study area, Penjwen district, is geographically situated between latitudes (35° 26' 30") and (35° 51' 40") North, and longitudes (45° 45' 05") and (46° 20' 57") East, encompassing a total area of (1138.56) km². This research aims to investigate the anthropogenic factors impacting the natural environment and agricultural ecosystems. The district's landscape has been subjected to significant environmental degradation, including deforestation, persistent soil pollution, and alteration of the natural topography. These adverse effects are manifested through the conversion of forested areas into agricultural land, the intensive application of chemical fertilizers (notably nitrogen, phosphorus, and potassium, and impacts on organic matter), and the widespread use of chemical pesticides to manage pests and plant diseases. The significance of this study lies in determining the optimal nutrient requirements for crop production, promoting the use of organic fertilizers as a substitute for chemical inputs, and utilizing diverse landforms for modern agricultural practices to prevent further deforestation. A key objective is to raise awareness among farmers regarding the environmental hazards associated with the overuse of chemical fertilizers and pesticides, which contributes to soil degradation. The ultimate goal is to conserve the district's natural environment and protect its soil as a vital natural resource.
Keywords: human activity; soil; agriculture Pinjwin; Environment